# 自动控制原理机械模型建模

f = m 1 x ¨ 1 + k 1 ( x 1 − x 2 ) + b 1 ( x ˙ 1 − x ˙ 2 ) f=m_1\ddot{x}_1+k_1(x_1-x_2)+b_1(\dot{x}_1-\dot{x}_2)

m 2 x 2 ¨ = k 1 ( x 1 − x 2 ) + b 1 ( x ˙ 1 − x ˙ 2 ) − b 2 x ˙ 2 m_2\ddot{x_2}=k_1(x_1-x_2)+b_1(\dot{x}_1-\dot{x}_2)-b_2\dot{x}_2

X 1 ( s ) F ( s ) = m 2 s 2 + ( b 1 + b 2 ) s + k Δ \frac{X_1(s)}{F(s)}=\frac{m_2s^2+(b_1+b_2)s+k}{\Delta}

X 2 ( s ) F ( s ) = b 1 s + k Δ \frac{X_2(s)}{F(s)}=\frac{b_1s+k}{\Delta}

Δ = m 1 m 2 s 4 + ( b 1 m 1 + b 2 m 1 + b 1 m 2 ) s 3 + ( k m 1 + b 1 b 2 + k m 2 ) s 2 + k b 2 s \Delta=m_1m_2s^4+(b_1m_1+b_2m_1+b_1m_2)s^3+(km_1+b_1b_2+km_2)s^2+kb_2s

f = m 1 x ¨ 1 + k 1 ( x 1 − x 2 ) + b 1 ( x ˙ 1 − x ˙ 2 ) + b 1 x ˙ 1 f=m_1\ddot{x}_1+k_1(x_1-x_2)+b_1(\dot{x}_1-\dot{x}_2)+b_1\dot{x}_1

m 2 x 2 ¨ = k 1 ( x 1 − x 2 ) + b 1 ( x ˙ 1 − x ˙ 2 ) m_2\ddot{x_2}=k_1(x_1-x_2)+b_1(\dot{x}_1-\dot{x}_2)

X 1 ( s ) F ( s ) = b 2 s + k Δ \frac{X_1(s)}{F(s)}=\frac{b_2s+k}{\Delta}

Δ = m 1 m 2 s 3 + ( b 2 m 1 + b 1 m 2 + k ) s 2 + ( k m 1 + b 1 b 2 + k m 2 ) s + k b 1 \Delta=m_1m_2s^3+(b_2m_1+b_1m_2+k)s^2+(km_1+b_1b_2+km_2)s+kb_1

m 1 x ¨ = − T 1 m_1\ddot{x}=-T_1

m 2 y ¨ = − k y + T 1 + T 2 m_2\ddot{y}=-ky+T_1+T_2

J θ ¨ = ( T 1 − T 2 ) r J\ddot{\theta}=(T_1-T_2)r

2 π r θ 2 π = x − y → r θ = y 2\pi r\frac{\theta}{2\pi}=x-y \rightarrow r\theta=y

Y ( s ) X ( s ) = − − 2 m 1 s 2 ( m 2 + J r 2 ) s 2 + k \frac{Y(s)}{X(s)}=-\frac{-2m_1s^2}{(m_2+\frac{J}{r^2})s^2+k}

J = 1 2 m 2 r J=\frac{1}{2}m_2r

m 1 x ¨ 1 = k 1 ( x 2 − x 1 ) m_1\ddot{x}_1=k_1(x_2-x_1)

f = m 2 x ¨ 2 + b x ˙ 2 + k 2 x 2 − k 1 ( x 1 − x 2 ) f=m_2\ddot{x}_2+b\dot{x}_2+k_2x_2-k_1(x_1-x_2)

X 1 ( s ) F ( s ) = k 1 m 1 m 2 s 4 + b m 1 s 3 + ( k 1 m 1 + k 2 m 1 + m 1 ) s 2 + b k 1 s + k 1 k 2 \frac{X_1(s)}{F(s)}=\frac{k_1}{m_1m_2s^4+bm_1s^3+(k_1m_1+k_2m_1+m_1)s^2+bk_1s+k_1k_2}

f 1 − b ( x ˙ 1 − x ˙ 2 ) = m 1 x ¨ 1 + k x 1 f_1-b(\dot{x}_1-\dot{x}_2)=m_1\ddot{x}_1+kx_1

f 2 + b ( x ˙ 1 − x ˙ 2 ) = m 2 x ¨ 2 + k x 2 f_2+b(\dot{x}_1-\dot{x}_2)=m_2\ddot{x}_2+kx_2
f 2 = 0 f_2=0
X 1 ( s ) F 1 ( s ) = m 2 s 2 + b s + k 2 Δ X 2 ( s ) F 1 ( s ) = b s Δ \frac{X_1(s)}{F_1(s)}=\frac{m_2s^2+bs+k_2}{\Delta} \quad \frac{X_2(s)}{F_1(s)}=\frac{bs}{\Delta}
f 1 = 0 f_1=0
X 1 ( s ) F 2 ( s ) = b s Δ X 2 ( s ) F 2 ( s ) = m 1 s 2 + b s + k 1 Δ \frac{X_1(s)}{F_2(s)}=\frac{bs}{\Delta} \quad \frac{X_2(s)}{F_2(s)}=\frac{m_1s^2+bs+k_1}{\Delta}

Δ = m 1 m 2 s 4 + b ( m 1 + m 2 ) s 3 + ( k 1 m 2 + k 2 m 1 ) s 2 + b ( k 1 + k 2 ) s + k 1 k 2 \Delta=m_1m_2s^4+b(m_1+m_2)s^3+(k_1m_2+k_2m_1)s^2+b(k_1+k_2)s+k_1k_2

11-17

04-19
07-28
09-26
10-27 1万+
12-07
07-26
04-24 9723
10-16
06-29
11-05 7016
01-08 497